2001
DOI: 10.1080/13576280110056618
|View full text |Cite
|
Sign up to set email alerts
|

Can Selection Assessments Predict Students' Achievements in the Premedical Year?: A Study at Arabian Gulf University

Abstract: Procedures for selecting students who are most likely to succeed academically in the initial year at an innovative medical school deserve further study and probably should include both academic performance and non-academic attributes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…One item (‘self-discipline is important’) with a factor loading of < 0.4 was deleted [20]. A confirmatory factor analysis was then used to verify the items ( p < .05) with an asymptotically distribution-free bootstrap model [21, 22] for construct validity testing and yielded moderate model fit. The Cronbach’s alpha was 0.874.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One item (‘self-discipline is important’) with a factor loading of < 0.4 was deleted [20]. A confirmatory factor analysis was then used to verify the items ( p < .05) with an asymptotically distribution-free bootstrap model [21, 22] for construct validity testing and yielded moderate model fit. The Cronbach’s alpha was 0.874.…”
Section: Methodsmentioning
confidence: 99%
“…Factor analysis revealed that the psychological (six items) and physical (four items) demands had factor loadings of 0.74–0.84 and 0.87–0.93, respectively. Confirmatory factor analyses was then used to verify the items ( p < .05) with an asymptotically distribution-free bootstrap model [21, 22] for construct validity testing and yielded good model fit. The Cronbach’s alpha for psychological and physical demands was 0.903 and 0.942, respectively (Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key attributes of confidence/self‐confidence include emotional intelligence/emotional competence, resilience (Abraham, 2004), confidence, attitude and cognitive ability (Al‐Nasir & Robertson, 2001), trust (Abraham, 2004), intuition (Koriat, 2008), narcissism (Campbell, Goodie, & Foster, 2004), depression (Stone, Dodrill, & Johnson, 2001), doubt, and uncertainty (De Cremer & Van Hiel, 2008). The attributes can positively or negatively affect confidence/self‐confidence and, as such, have been subdivided into positive and negative attributes (Table 2).…”
Section: Methods Of Concept Analysis and Applicationmentioning
confidence: 99%
“…Al‐Nasir and Robertson (2001) report that personal characteristics and attitudes include confidence as an attribute, as well as cognitive abilities that affect confidence and may predict success. According to Belcher and Jones (2009) a lack of confidence means that new graduate nurses are unlikely to trust themselves.…”
Section: Methods Of Concept Analysis and Applicationmentioning
confidence: 99%